ド・モルガンの法則とその証明

ド・モルガンの法則

ド・モルガンの法則
(A\cup B)^{c} = A^c \cap B^c

一般に:(\displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda})^c = \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c

(A\cup B)^{c} = A^c \cap B^c

証明

(A\cup B)^{c} = A^c \cap B^c を示す。

(\subset)

x \in (A\cup B)^{c} とする。

x\notin A\cup B.

x\notin A かつ x\notin B.

x\in A^c かつ x\in B^c.

x\in A^c \cap B^c.

したがって, (A\cup B)^{c} \subset A^c \cap B^c

(\supset)

x\in A^c \cap B^c とする。

x\in A^c かつ x \in B^c

x \notin A かつ x \notin B

x \notin A\cup B

x \in (A\cup B)^c.

したがって, (A\cup B)^{c} \supset A^c \cap B^c

結論

(\subset) と (\supset) を合わせて,

(A\cup B)^{c} = A^c \cap B^c.

一般に:(\displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda})^c = \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c

証明

(\displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda})^c = \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c を示す。

(\subset)

x \in (\displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda})^c とする。

x\notin \displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda}.

x\notin A_\lambda  ({}^{\forall}\lambda\in\Lambda).

x\in A_\lambda^c ({}^{\forall}\lambda\in\Lambda).

x\in \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c.

したがって, (\displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda})^c \subset \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c

(\supset)

x\in \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c とする。

x\in A_\lambda^c({}^{\forall}\lambda\in\Lambda)

x \notin A_{\lambda} ({}^{\forall}\lambda\in\Lambda)

x \notin \displaystyle\bigcup_{\lambda\in\Lambda} A_\lambda

x \in (\displaystyle\bigcup_{\lambda\in\Lambda} A_\lambda)^c.

したがって, (\displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda})^c \supset \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c

結論

(\subset) と (\supset) を合わせて,

(\displaystyle\bigcup_{\lambda\in \Lambda} A_{\lambda})^c = \displaystyle\bigcap_{\lambda\in\Lambda} A_\lambda^c.